(untitled) (Architecture Image Studies, 2024)
Imam Reza (AS)’s Hejrat to Iran, as the greatest religious event in the history of Iran and the spiritual works and important blessings of this wonderful trip in Iran have been left. One of these works is the Ghadamghah attributed to that Imam, which has been considered by Razavi enthusiasts and pilgrims in different cities and regions. The purpose of this article is to recognize the Ghadamghahs of Imam Reza (as) in Iran in order to protect, maintain and develop these Ghadamghah as places of pilgrimage. This research has been done by historical, analytical and interdisciplinary research methods and by using documentary study methods, libraries and case studies. The results of this study show that the Ghadamghah attributed to Imam Reza (AS) are located from southwest to northeast of Iran in Khuzestan, Fars, Yazd and Khorasan regions. The most important of these Ghadamghah include Shalamcheh, Arjan, Ali Ibn Mahziar, Morteza Ali in Eghlid Fars, Abarkooh and Yazd Ghadamghah, Deh Shir Ghadamghah, Taft Ghadamghah, Mashhadak Khoranagh Ghadamghah, Deh Sorkh Ghadamghah and Neishabour Ghadamghah. Pedestrians as centers of pilgrimage and religious tourism need to strengthen and create the necessary infrastructure in various dimensions, including facilities and equipment for public transport, welfare, recreation and recreation, health and safety, safety and security, signs and symbols and It is memorable.